Hydrogen storage in nanoporous carbon materials: myth and facts - Kowalczyk, Poitr; Holyst, R.; Terrones, M.; Terrones, H. (Royal Society of Chemistry, 2007)
We used Grand canonical Monte Carlo simulation to model the hydrogen storage in the primitive, gyroid, diamond, and quasi-periodic icosahedral nanoporous carbon materials and in carbon nanotubes. We found that none of the investigated nanoporous carbon materials satisfy the US Department of Energy goal of volumetric density and mass storage for automotive application (6 wt% and 45 kg H2 m3) at considered storage condition. Our calculations indicate that quasi-periodic icosahedral nanoporous carbon material can reach the 6 wt% at 3.8 MPa and 77 K, but the volumetric density does not exceed 24 kg H2 m3. The bundle of single-walled carbon nanotubes can store only up to 4.5 wt%, but with high volumetric density of 42 kg H2 m3. All investigated nanoporous carbon materials are not effective against compression above 20 MPa at 77 K because the adsorbed density approaches the density of the bulk fluid. It follows from this work that geometry of carbon surfaces can enhance the storage capacity only to a limited extent. Only a combination of the most effective structure with appropriate additives (metals) can provide an efficient storage medium for hydrogen in the quest for a source of ‘‘clean’’ energy.